2013
DOI: 10.1186/1471-2393-13-69
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of unintended pregnancy among women in Nairobi, Kenya

Abstract: BackgroundThe prevalence of unintended pregnancy in Kenya continues to be high. The 2003 Kenya Demographic and Health Survey (KDHS) showed that nearly 50% of unmarried women aged 15–19 and 45% of the married women reported their current pregnancies as mistimed or unwanted. The 2008–09 KDHS showed that 43% of married women in Kenya reported their current pregnancies were unintended. Unintended pregnancy is one of the most critical factors contributing to schoolgirl drop out in Kenya. Up to 13,000 Kenyan girls d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
145
17
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(206 citation statements)
references
References 38 publications
41
145
17
3
Order By: Relevance
“…It is noteworthy that married women in our study reported a prevalence of unwanted pregnancy of 32%. This was much higher than 13% reported for married women in both Kenya and Eastern Sudan 20,23 . The findings suggest that hairdressers may be at increased risk of unwanted pregnancies.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…It is noteworthy that married women in our study reported a prevalence of unwanted pregnancy of 32%. This was much higher than 13% reported for married women in both Kenya and Eastern Sudan 20,23 . The findings suggest that hairdressers may be at increased risk of unwanted pregnancies.…”
Section: Discussioncontrasting
confidence: 57%
“…Overall prevalence of unwanted pregnancy was 24% among women in both Ethiopia and Kenya and 26% in Iran [19][20][21] . In Nigeria, about one-fourth of women in a study conducted in eight states reported unwanted pregnancy 22 .…”
Section: Discussionmentioning
confidence: 99%
“…For example a study done in Kenya showed that women with at least secondary education had their first sexual intercourse delayed by at least three years [14] (Figure 3 In this study, occupation was not associated with prevalence of unwanted pregnancy. This may be due to high number of study participants had their own job and civil servants.…”
Section: Independent Predictors Of Unwanted Pregnancymentioning
confidence: 72%
“…al. 2002), 43% in Kenya (Ikamari et. al 2013), 43% in Nigeria (Nwokocha, 2006), 35% in both Iran (AbbasiShavazi et.…”
Section: Introductionmentioning
confidence: 99%